Self-Disclosure Among Social Media Influencers in Padang City: A Phenomenological Study of Forms, Motivations, Impacts, and Challenges - Sofia Adinda Putri; Niken Hartati (Da'wa Faculty of Islamic State University Salatiga, 2025)
This study examines how three Padang-based influencersBintang Fakhirin, Ni Mida (Ratu Deslim), and Wahyu Hidayat negotiate self-disclosure within a collectivist cultural context. Using a phenomenological approach, in-depth interviews conducted in May 2024 revealed four key themes: forms of disclosure, motivations, perceived impacts, and challenges. Findings show that disclosure is driven by emotional needs, extroverted personalities, and economic opportunities, but constrained by communal judgment, linguistic stigmatization, and phone dependence. These practices reflect a negotiation between authenticity and cultural expectations, aligning with Altman and Taylor’s Social Penetration Theory, DeVito’s disclosure dimensions, and Goffman’s dramaturgical model. By situating self-disclosure within the Minangkabau cultural setting, the study highlights how collectivist values and the principle of adat basandi syarak, syarak basandi Kitabullah shape digital practices. Practically, it underscores the importance of culturally sensitive strategies, digital literacy, and psychosocial support.